COMPARISON OF THE DHIKR THE SAMMANIYAH AND NAQSABANDIYAH ORDERS IN MEDAN CITY - Ahmad Yudha Ritonga; Wahyu Wiji Utomo (International Journal of Cultural and Social Science, 2025)
Dhikr as the core of spiritual teachings and practices in Sufi orders, especially the Sammaniyah and Naqsabandiyah orders which are rapidly developing in Medan City. This study aims to compare the procedures, meanings, and socio-spiritual implications of the dhikr of the two orders, considering the fundamental differences between the dhikr jahr (loud) which is the characteristic of Sammaniyah and the dhikr khafi (silent) which is the identity of Naqsabandiyah. The research method used is a qualitative approach with field research and comparative studies, where data are collected through observation, interviews with mursyid and congregation in the field. The results of the study show that the Sammaniyah Order in Medan emphasizes dhikr jahr in congregation with the accompaniment of ratib, qasidah, and elements of body movement that create a dynamic spiritual atmosphere, while the Naqsabandiyah Order emphasizes dhikr khafi which is carried out individually or in small groups in a quiet and contemplative atmosphere. Both orders equally emphasize external and internal manners, as well as consistency in dhikr as a way of cleansing the soul and forming spiritual character. Where here we will find out how we can do dhikr for everyday life by knowing the dhikr in a congregation. The differences in dhikr methods create diversity in Sufism traditions but enrich Muslims' faith in Allah SWT.